Застосування когнітивних карт для дослідження проблем підвищення якості життя населення в умовах міжрегіональної диференціації - Tyushnyakov, Vitaly; Tkachenko, Yulia (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
This paper studies issues of the rise in the standards of living and improvement of the quality of life of the population in the frame of intermunicipal disparities. Simulation and modelling are examined in relation to research of standards of living and quality of life. Tools of cognitive modelling and simulation are used to acquire new knowledge on the regional social and economic, ecological, and political system which determines the standards of living and quality of life. A cognitive model studying the quality of life was designed and its structural properties were analyzed. Scenarios were created to model possible developments of the situation under the influence of various factors. The novelty of the work is in applying a new informational technology of cognitive modelling to studying the improvement of the quality of life in the frame of intermunicipal disparities.